2020
DOI: 10.32615/ps.2020.006
|View full text |Cite
|
Sign up to set email alerts
|

Special issue in honour of Prof. Reto J. Strasser - Monitoring seasonal damage of photosynthetic apparatus in mature street trees exposed to road-side salinity caused by heavy traffic

Abstract: De-icing salts are harmful for roadside greenery. The aim of our study was to examine photosystem II performance in mature trees growing along a road of heavy traffic in relation to shoot and soil salinity caused by de-icing salts. Leaves from each three specimens of Aesculus hippocastanum, Tilia cordata, and Betula pendula growing along the same road, nine leaves from a roadside part (RS) and nine from an opposite part (OS) of each tree crown, were sampled in June, July, and September, 2017 and 2018. The PSII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 67 publications
0
7
0
1
Order By: Relevance
“…During the growing season, the number of active RCs in leaf tissues decreased month by month [ 60 , 110 ]. However, in mid-summer, the density of active RCs in damaged trees was significantly lower while at the end of autumn the opposite trend was observed, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the growing season, the number of active RCs in leaf tissues decreased month by month [ 60 , 110 ]. However, in mid-summer, the density of active RCs in damaged trees was significantly lower while at the end of autumn the opposite trend was observed, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in the photosynthesis process can be caused by abiotic or biotic stresses and are possible to be found before the occurrence of visible symptoms of tree deterioration (leaf chlorosis, necrosis and growth limitation) [ 55 , 56 ]. Reported studies have confirmed its usefulness for the assessment of resistance to drought and other stress factors occurring in human-affected environments [ 57 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…Salinity causes reductions in leaf area in several agronomic and forest species ( Sun et al, 2018 ), and this may explain the low NDVI values observed in the present study. Leaf area reduction is a morphological modification by plants to avoid water loss by transpiration, but this adaptation also significantly reduces the photosynthetic activity ( Swoczyna & Latocha, 2020 ). For this reason, both growth and productivity are commonly affected in saline ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, soil conservation programs are still necessary in southern Sonora, since this region is located in the vicinity of the coastal zone. This is the main factor that contributes to the salinization and natural sodification as geological phenomena that increase the salt concentration in Sonoran groundwater ( Swoczyna & Latocha, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the complexity of factors affecting woody plants and the variability in the intensity of these factors during their life (extreme summers or winters, human-induced changes in the soil environment, etc.) can sometimes make it difficult to explain the background of the responses of the trees/shrubs studied ( Swoczyna and Latocha, 2020 ). The complexity of environmental conditions may affect the magnitude and duration of the response to stress, e.g., limited access to nitrogen in the soil may increase the effect of drought stress, triggering a change in growth strategy and physiology ( Ögren, 1988 ).…”
Section: Introductionmentioning
confidence: 99%